2019
DOI: 10.1016/j.neubiorev.2019.06.036
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on the head direction cell system and spatial behavior

Abstract:  Damage to the head direction circuit produces only modest impairments in spatial behavior.  Head direction cells predict spatial behavior in some tasks, but not others.  New evidence suggests that there are different kinds of head direction cells.  Different head direction cells may underlie different spatial abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 115 publications
(121 reference statements)
4
38
0
Order By: Relevance
“…HD-cells reference facing direction relative to known landmarks (Taube and Burton, 1995) and are often compared to an 'internal compass' mediating our sense of direction (Butler et al, 2017;Cullen and Taube, 2017). This HD-cell compass plays a central role in cognitive mapping and is thought to mediate homing, reorientation and path integration behavior (Butler et al, 2017;Cullen and Taube, 2017;Dudchenko et al, 2019;van der Meer et al, 2010;Valerio and Taube, 2012;Weiss and Derdikman, 2018;Weiss et al, 2017). We observed that multiple brain areas encoded direction, many of which overlap with regions known to contain HDcells in rodents and monkey.…”
Section: Visual Information and Head Directionmentioning
confidence: 84%
See 3 more Smart Citations
“…HD-cells reference facing direction relative to known landmarks (Taube and Burton, 1995) and are often compared to an 'internal compass' mediating our sense of direction (Butler et al, 2017;Cullen and Taube, 2017). This HD-cell compass plays a central role in cognitive mapping and is thought to mediate homing, reorientation and path integration behavior (Butler et al, 2017;Cullen and Taube, 2017;Dudchenko et al, 2019;van der Meer et al, 2010;Valerio and Taube, 2012;Weiss and Derdikman, 2018;Weiss et al, 2017). We observed that multiple brain areas encoded direction, many of which overlap with regions known to contain HDcells in rodents and monkey.…”
Section: Visual Information and Head Directionmentioning
confidence: 84%
“…First, these cells provide a directional representation that is continuous (i.e. they always maintain similar activity on population-level following attractor-dynamics (Cullen and Taube, 2017;Dudchenko et al, 2019;Skaggs et al, 1995;Taube, 2007). Second, impairments or even lesions of the HD-cell system only have very moderate effects on behavior (Dudchenko et al, 2019).…”
Section: Visual Information and Head Directionmentioning
confidence: 99%
See 2 more Smart Citations
“…HD cells reference facing direction relative to known landmarks 47 and are often compared with an internal compass mediating our sense of direction 45,48 . This HD-cell compass plays a central role in cognitive mapping and is thought to mediate homing, reorientation, and pathintegration behavior 45,[48][49][50][51][52][53] . We observed that multiple brain areas encoded direction, many of which overlap with regions known to contain HD cells in rodents and monkeys.…”
Section: Discussionmentioning
confidence: 99%